Laminate, molded body, and method for producing molded body

JP7631236B2Active Publication Date: 2025-02-18IDEMITSU UNITECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021571200
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-01-14
Filing Date
2021-01-13
Publication Date
2025-02-18
Estimated Expiration
2041-01-13

Smart Images

  • Figure 0007631236000002
    Figure 0007631236000002
  • Figure 0007631236000001
    Figure 0007631236000001
Patent Text Reader

Abstract

A laminate including: a resin layer that includes a polypropylene with a crystallization speed of 2.5 min-1 or less at 130°C; and an easily-adhering layer, wherein the easily-adhering layer includes a crosslinked body that is obtained by crosslinking a resin using a crosslinking agent that has at least one type of group selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate, a molded body, and a method for producing a molded body. [Background technology]

[0002] Polypropylene sheets are excellent in formability, heat resistance, solvent resistance, etc., and are therefore used as thermoformed containers and decorative sheets for decorative molding. However, polypropylene has the disadvantage of poor adhesion to coatings, painting, and printing. To compensate for this disadvantage, a technique for forming a thin film such as a primer or an easy-adhesion layer in advance is sometimes used.

[0003] Incidentally, a technique is known in which, when printing is performed on a stretched (oriented) polypropylene film, a coating layer containing a crosslinking agent is formed on the film in advance (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-006181 A [Patent Document 2] JP 2016-168685 A Summary of the Invention

[0005] In thin films such as primers and easy-adhesion layers, when a three-dimensional crosslinking structure is introduced using a crosslinking agent to reduce the effects of impregnation with coating, painting, printing solvents, photocurable resins, etc., it is expected that the solvent resistance will improve, but the flexibility of the thin film will be impaired, and the thin film may crack during thermoforming, causing poor appearance and uneven thickness of the sheet, i.e., it may become unsuitable for thermoforming. On the other hand, if a crosslinking agent is not used, impregnation with painting or printing solvents may cause design defects and deteriorate printability. Incidentally, stretched (oriented) polypropylene films are not usually used in thermoforming processes.

[0006] An object of the present invention is to provide a laminate which has high coatability and can maintain its design even after molding.

[0007] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a specific crosslinking agent in the adhesion layer, and have completed the present invention. According to the present invention, the following laminate and the like are provided. 1.Crystallization speed at 130℃ is 2.5min -1 A laminate comprising a resin layer containing the following polypropylene and an easy-adhesion layer, The easy-adhesion layer includes a crosslinked body obtained by crosslinking a resin with a crosslinking agent having one or more groups selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group. Laminate. 2. The laminate according to 1 above, wherein the crosslinking agent is a crosslinking agent having a carbodiimide group. 3. The laminate according to 1 or 2 above, wherein the resin in the easy-adhesion layer contains one or more resins selected from the group consisting of urethane resins, acrylic resins, polyolefin resins, and polyester resins. 4. The laminate according to any one of 1 to 3 above, wherein the resin in the easy-adhesion layer includes a urethane resin. 5. The laminate according to any one of 1 to 4 above, wherein the amount of the crosslinking agent is 2 to 50 parts by mass with respect to 100 parts by mass of the resin. 6. The laminate according to any one of 1 to 5 above, wherein the polypropylene has an isotactic pentad fraction of 80 mol % or more and 99 mol % or less. 7. The laminate according to any one of 1 to 6 above, wherein the resin layer does not contain a nucleating agent. 8. The laminate according to any one of 1 to 7 above, further comprising a coating layer on a part or the entire surface of the easily adhesive layer opposite to the resin layer. 9. The laminate according to any one of 1 to 7 above, further comprising a printed layer on a part of or the entire surface of the easily adhesive layer opposite to the resin layer. 10. The laminate according to any one of 1 to 7 above, further comprising a coating layer on a part or the entire surface of the easily adhesive layer opposite to the resin layer. 11. A molded article produced using the laminate described in any one of 1 to 10 above. 12. A method for producing a molded article, comprising molding the laminate described in any one of 1 to 10 above. 13. The method for producing a molded product according to claim 12, further comprising the steps of: placing the laminate in a mold; supplying molding resin to be integrated with the laminate; and carrying out the molding. 14. A method for producing a molded body as described in 12, comprising shaping the laminate to fit a mold, attaching the shaped laminate to the mold, supplying molding resin to integrate it with the shaped laminate, and performing the molding. 15. A method for producing a molded body as described in 12, comprising disposing a core material in a chamber box, placing the laminate above the core material, heating and softening the laminate, and reducing the pressure inside the chamber box to press the heat-softened laminate against the core material to cover it. 16. A method for producing a molded body, comprising painting a part or the entire surface of the easy-adhesion layer of the molded body produced by the method for producing a molded body according to any one of 12 to 15, the surface being opposite the resin layer. 17. A method for producing a molded body, comprising printing on a part or the entire surface of the easy-adhesion layer of the molded body produced by the method for producing a molded body described in any one of 12 to 15, the surface being opposite to the resin layer.

[0008] According to the present invention, it is possible to provide a laminate which has high coatability and can maintain its design even after molding. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of an example of a manufacturing apparatus for manufacturing a laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The laminate, the molded product, and the method for producing the molded product according to the present invention will be described below. In this specification, "x to y" represents a numerical range of "not less than x and not more than y". The upper and lower limit values ​​described in the numerical range can be arbitrarily combined. In addition, any combination of two or more of the individual aspects of the present invention described below is also an aspect of the present invention.

[0011] 1.Laminate The laminate according to one embodiment of the present invention has a crystallization rate of 2.5 min at 130° C. -1 The resin layer includes the following polypropylene (hereinafter, also referred to as "polypropylene X"), and an easy-adhesion layer. The easy-adhesion layer contains a crosslinked body obtained by crosslinking a resin with a crosslinking agent (hereinafter also referred to as "crosslinking agent Y") having one or more groups selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group.

[0012] The laminate according to one embodiment of the present invention has high coatability and can maintain its design even after a molding process. The reasons for such effects are presumed to be as follows. The resin contained in the easy-adhesion layer is densified by the crosslinked structure caused by the crosslinking agent Y. Therefore, even if a coating layer is provided on the easy-adhesion layer by coating, painting, or printing, the coating liquid or solvent is prevented from penetrating into the easy-adhesion layer. As a result, bleeding, unevenness, streaks, repelling, and whitening in the coating layer are prevented, and the intended design is easily reproduced. In other words, the deterioration of design can be suppressed, and the coating property is excellent. Furthermore, the adhesive layer is interposed between the resin layer and the coating layer, so that the adhesion between them is high, and further, the adhesive layer is crosslinked by the crosslinking agent Y to improve its chemical resistance and flexibility compared to crosslinking agents other than the crosslinking agent Y. Therefore, cracks and thickness deviations during thermoforming, as well as cracks and peeling of the coating layer, can be prevented, and the design of the coating layer can be maintained. In addition, the fact that the crosslinking agent Y can be crosslinked at a relatively low temperature also contributes to improving moldability. That is, since the crosslinking agent Y can be crosslinked at a relatively low temperature, an easy-adhesion layer can be formed on the resin layer at a relatively low temperature. Therefore, it is possible to prevent the polypropylene X from whitening during molding, which would impair the design. In addition, the crosslinking agent Y has a relatively long pot life after mixing the resin and the crosslinking agent when forming the adhesive layer (when applying), so that the adhesive layer can be stably formed. Furthermore, the crosslinking agent Y has low toxicity and is therefore excellent in safety.

[0013] [Resin layer] The polypropylene X contained in the resin layer is a polymer containing at least propylene as a monomer unit. Specific examples include homopolypropylene, copolymers of propylene and olefin, etc. Homopolypropylene is preferred because of its excellent heat resistance and hardness. The copolymer of propylene and an olefin may be a block copolymer or a random copolymer, or a mixture thereof. Examples of the olefin include ethylene, butylene, and cycloolefin.

[0014] The crystallization rate of polypropylene X at 130℃ is 2.5min -1 The following is the result. In one embodiment, the crystallization rate is 2.0 min -1 Below, 1.5min -1 Below, 1.0 min -1 Below, 0.8min -1 Less than or equal to 0.6min -1 The lower limit is not particularly limited, for example, 0.05 min. -1 That's all. The crystallization speed is 2.5 min -1 By satisfying the above condition, whitening of the resin layer due to molding can be prevented. In addition, when the heat-softened resin layer is cooled and hardened in a mold or the like, unevenness in the degree of hardening is unlikely to occur, so that extensibility is improved. As a result, molding precision is improved, and it becomes easy to impart complex shapes and fine irregularities to the laminate. The crystallization rate is measured by the method described in the Examples.

[0015] The isotactic pentad fraction of the polypropylene X is preferably 80 mol % or more and 99 mol % or less. In one embodiment, the isotactic pentad fraction of the polypropylene X is 80 mol% or more, 82 mol% or more, 85 mol% or more, 86 mol% or more, 87 mol% or more, 88 mol% or more, 89 mol% or more, 90 mol% or more, or 91 mol% or more, and is 99 mol% or less, or 98 mol% or less. By setting the isotactic pentad fraction to 80 mol % or more, excellent rigidity is imparted to the molded article obtained by molding the laminate, while by setting the isotactic pentad fraction to 99 mol % or less, whitening of the resin layer during molding is further prevented. The isotactic pentad fraction is the isotactic fraction of pentad units (five consecutive propylene monomers isotactically bonded) in the molecular chain of the resin composition. The method for measuring this fraction is described, for example, in Macromolecules, Vol. 8 (1975), p. 687, 13 It can be measured by C-NMR. The isotactic pentad fraction is measured by the method described in the Examples.

[0016] In one embodiment, the polypropylene X contains smectic crystals as a crystal structure. Polypropylene is a crystalline resin and can take crystalline forms such as α-crystals, β-crystals, γ-crystals, and smectic crystals. Of these crystalline forms, smectic crystals can be generated as an intermediate between amorphous and crystalline by cooling polypropylene from a molten state at a rate of 80°C / sec or more. Smectic crystals are not stable structures with regular structures like crystals, but are metastable structures in which fine structures are gathered together. Therefore, the interactions between molecular chains are weak, and compared to stable structures such as α-crystals, the resin layer can be softened with a low amount of heat, resulting in excellent moldability. In addition to Smectic crystals, the polypropylene X may contain other crystal forms such as β crystals, γ crystals, amorphous parts, etc. For example, 30% by mass or more, 50% by mass or more, 70% by mass or more, or 90% by mass or more of the polypropylene X may be Smectic crystals. When the laminate is molded to obtain a molded product, the Smectic crystals can transform into α crystals while maintaining the fine structure derived from the Smectic crystals, which can further improve the surface hardness and transparency. By calculating the scattering intensity distribution and long period by small angle X-ray scattering analysis, it is possible to determine whether the resin layer was obtained by cooling at 80°C / sec or more. In other words, this analysis makes it possible to determine whether the resin layer contains Smectic crystals (whether it has a fine structure derived from Smectic crystals). The measurements are carried out under the following conditions: The X-ray generator used is ultraX 18HF (manufactured by Rigaku Corporation), and an imaging plate is used to detect scattering. ·Light source wavelength: 0.154nm Voltage / Current: 50kV / 250mA Irradiation time: 60 minutes Camera length: 1.085m - The laminates are stacked so that the sample thickness is 1.5 to 2.0 mm. Also, the laminates are stacked so that the film formation (MD) direction is aligned.

[0017] In one embodiment, the polypropylene X preferably has an exothermic peak of 1.0 J / g or more (more preferably 1.5 J / g or more) on the low temperature side of the maximum endothermic peak in a differential scanning calorimeter curve. The upper limit is not particularly limited, but is usually 10 J / g or less. The exothermic peak is measured using a differential scanning calorimeter.

[0018] The resin layer preferably contains a small amount of nucleating agent, and more preferably does not contain a nucleating agent. The content of the nucleating agent in the resin layer is preferably 1.0 mass% or less, more preferably 0.5 mass% or less, based on the total amount of the resin layer. Examples of the nucleating agent include sorbitol-based nucleating agents, and commercially available products include Gelall MD (Shin-Nihon Rikagaku Co., Ltd.) and Rikemaster FC-1 (Riken Vitamin Co., Ltd.).

[0019] One method for making polypropylene, a crystalline resin, transparent is to forcibly generate fine crystals by adding a nucleating agent. In this method, the crystallization rate is accelerated by the nucleating agent, which generates a large number of crystals to create a highly packed state, thereby limiting the space in which each crystal physically grows, thereby making the crystals finer. However, since the nucleating agent contains a substance that acts as a nucleus, the product usually has a slight whitish tinge. In addition, the crystallization rate at 130°C can be increased by 2.5 min -1 If the speed is increased beyond this, whitening of the resin layer occurs during molding. In contrast, even if the content of nucleating agent is low or not included, the crystallization rate of polypropylene X at 130°C is 2.5 min -1 By satisfying the above conditions, whitening can be prevented and a molded product having excellent design (appearance) can be obtained.

[0020] In one embodiment, the polypropylene X has a long chain branching structure. The branching index g' is an index of whether or not the polypropylene X has a long chain branched structure. The branching index g' is defined as follows. Branching index g'=[η] br / [η] lin [η] br : Intrinsic viscosity of polymer (br) having long chain branch structure [η] lin : Intrinsic viscosity of a linear polymer having the same molecular weight as the polymer (br) As is clear from the above, when g'<1, it is determined that the polypropylene X has a long chain branch structure, and the smaller the g' value, the more the long chain branch structure is contained. Here, the intrinsic viscosity is a value measured at 140°C. When polypropylene X has a long chain branched structure, the branching index g' thereof may be 0.50 or more and less than 1.00. An example of a commercially available polypropylene having a long chain branched structure is "Waymax MFX6" manufactured by Japan Polypropylene Corporation. Since the polypropylene X has a long chain branched structure, it exhibits high melt tension and can suppress drawdown caused by heating during molding (for example, vacuum molding, pressure molding, or vacuum pressure molding).

[0021] The resin layer may contain components other than the polypropylene X. Examples of the other components include other resin components, metal foil powder, pearl pigments, colorants, and other additives.

[0022] Examples of other resin components include elastomers. Examples of elastomers include thermoplastic elastomers such as olefin-based elastomers, styrene-based elastomers, polyvinyl chloride-based elastomers, urethane-based elastomers, polyester-based elastomers, and polyamide-based elastomers. In one embodiment, the thermoplastic elastomer is an olefin-based elastomer. Examples of the olefin-based elastomers include commercially available products such as "Engage 8200" manufactured by The Dow Chemical Company. The content of the other resin components in the resin layer is, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the polypropylene X.

[0023] Examples of the metal foil powder include crushed irregular flat flakes obtained by crushing a sheet in which both sides of a metal thin film layer are covered with a transparent thin film layer, etc. Examples of the pearl pigment include irregular flat flakes mainly composed of mica. The content of the metal foil powder or pearlescent pigment in the resin layer is, for example, 0.1 parts by mass or more and, for example, 5 parts by mass or less, relative to 100 parts by mass of the polypropylene X.

[0024] As the colorant, for example, a general colorant such as an organic pigment, an inorganic pigment, or a dye can be used, but it is not limited thereto. The content of the colorant in the resin layer is, for example, 0.1 parts by mass or more and, for example, 30 parts by mass or less, relative to 100 parts by mass of the polypropylene X.

[0025] Examples of other additives include, but are not limited to, ultraviolet absorbers, hindered amine weathering agents, antistatic agents, antioxidants, slip agents, antiblocking agents, anti-dye agents, lubricants, and the above-mentioned nucleating agents. The content of other additives in the resin layer is, for example, 0.1 parts by mass or more and, for example, 10 parts by mass or less, based on 100 parts by mass of polypropylene X. The content of the nucleating agent is as described above.

[0026] In one embodiment, the resin layer consists solely of polypropylene X, or consists essentially solely of polypropylene X. In the latter case, the resin layer may contain unavoidable impurities. In one embodiment, the resin layer is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass Polypropylene X or Polypropylene X and one or more components selected from the other components listed above.

[0027] The thickness of the resin layer is not particularly limited. In one embodiment, the thickness of the resin layer is 10 μm or more, 20 μm or more, or 30 μm or more, and 1000 μm or less, 800 μm or less, 500 μm or less, or 400 μm or less.

[0028] The method for forming the resin layer is not particularly limited, and examples thereof include an extrusion method. In the extrusion method, the resin layer is cooled from the molten state at a rate of preferably 80° C. / sec or more until the internal temperature of the resin layer becomes equal to or lower than the crystallization temperature of polypropylene. This increases the crystallization rate of the polypropylene contained in the resin layer at 130° C. to 2.5 min. -1Cooling can be at least 90° C. / sec, at least 100° C. / sec, at least 110° C. / sec, at least 120° C. / sec, at least 130° C. / sec, at least 140° C. / sec, or at least 150° C. / sec.

[0029] In one embodiment, the resin layer is not stretched (has not been subjected to a stretching step). By the resin layer being unstretched, it has excellent suitability for molding.

[0030] [Easy adhesive layer] The crosslinked body contained in the easy-adhesion layer is obtained by crosslinking a resin with a crosslinking agent Y. The crosslinking agent Y is a crosslinking agent having one or more functional groups selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group.

[0031] The crosslinking agent Y can have two or more crosslinkable functional groups in the molecule for crosslinking the resin, and can include one or more functional groups selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group as such crosslinkable functional groups. In one embodiment, the molecular weight of the crosslinkable functional group in 1 mole of the crosslinking agent Y is 50 or more, 100 or more, or 120 or more. The upper limit is not particularly limited, and is, for example, 1000 or less.

[0032] Examples of crosslinking agents having a carbodiimide group include polycarbodiimide, etc. Examples of commercially available products include Carbodilite V-10 (manufactured by Nisshinbo Chemical Inc.).

[0033] Examples of crosslinking agents having an oxazoline group include water-soluble oxazoline group-containing polymers, etc. Examples of commercially available products include EPOCROS WS-500 (manufactured by Nippon Shokubai Co., Ltd.).

[0034] Examples of the crosslinking agent having an aziridine group include aziridine compounds, etc. Examples of commercially available products include Chemitite (manufactured by Nippon Shokubai Co., Ltd.).

[0035] In one embodiment, the crosslinking agent Y is a crosslinking agent containing one or more functional groups selected from the group consisting of a carbodiimide group and an oxazoline group, which improves safety to the human body. In one embodiment, the crosslinking agent Y is a crosslinking agent having a carbodiimide group. A crosslinking agent having a carbodiimide group is capable of crosslinking even at room temperature (20° C.), and the effects of the present invention are significantly exhibited.

[0036] The resin to be crosslinked by the crosslinking agent Y is not particularly limited. The resin crosslinked by the crosslinking agent Y preferably contains one or more selected from the group consisting of urethane resin, acrylic resin, polyolefin resin, and polyester resin. If these resins are used, even when the laminate is molded into a complex non-planar shape, the easy-adhesion layer follows the resin layer to maintain the laminate structure, thereby preventing cracks and peeling.

[0037] The urethane resin is not particularly limited, and examples thereof include urethane resins obtained by reacting diisocyanate, high molecular weight polyol, and a chain extender. As the high molecular weight polyol, polyether polyol or polycarbonate polyol may be used. Examples of commercially available products include Hydran WLS-202 (manufactured by DIC Corporation).

[0038] The acrylic resin is not particularly limited, and examples of commercially available products include Acrylit 8UA-366 (manufactured by Taisei Fine Chemical Co., Ltd.).

[0039] The polyolefin resin is not particularly limited, and examples thereof include polyethylene, polypropylene, cyclic polyolefin, etc. Commercially available products include Arrowbase DA-1010 (manufactured by Unitika Ltd.).

[0040] The polyester resin is not particularly limited, and examples thereof include polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate.

[0041] The above-mentioned resins, particularly polyolefin resins and polyester resins, may be modified resins into which a functional group capable of crosslinking with the crosslinking agent Y has been introduced. The functional group capable of crosslinking with the crosslinking agent Y is not particularly limited, and may be, for example, a carboxy group.

[0042] The resin crosslinked by the crosslinking agent Y preferably contains a urethane resin from the viewpoints of adhesion to a coating layer (such as a printed layer, a painted layer, a coating layer, etc.) laminated on the easy-adhesion layer and formability.

[0043] The compounding ratio of the resin and the crosslinking agent Y in the easy-adhesion layer is not particularly limited. In one embodiment, the amount of crosslinking agent Y in the easy-adhesion layer is 2 parts by mass or more, 4 parts by mass or more, 6 parts by mass or more, or 10 parts by mass or more, and 50 parts by mass or less, 45 parts by mass or less, 40 parts by mass or less, or 35 parts by mass or less, per 100 parts by mass of the resin. When the blending amount of the crosslinking agent Y is 2 to 50 parts by mass relative to 100 parts by mass of the resin, the crosslinking reaction proceeds smoothly, and the effects of the present invention are well exhibited.

[0044] Even after the crosslinking is completed, the blending ratio of the resin used to form the easy-adhesion layer in the laminate or molded product and the crosslinking agent Y can be calculated by Fourier transform infrared spectroscopy (FTIR). The measurement is performed under the following conditions. The measurement device used is the FT / IR-6100 manufactured by JASCO Corporation, and the surface of the easy-adhesion layer side of the laminate is attached to a prism using the attenuated total reflection (ATR) method to obtain an absorption spectrum. Samples with different resin and crosslinker content ratios are prepared in advance, and a calibration curve is created using the absorbance ratio of the peaks originating from the resin and crosslinker in the measured spectrum, allowing the blending ratio of the resin and crosslinker to be determined. If printing or painting is applied to the surface opposite the resin layer of the easy-adhesion layer, the easy-adhesion layer cannot be directly measured by the ATR method. In this case, the laminate or molded body on which printing or painting is applied is cut obliquely from the easy-adhesion layer side at an angle of 1000:1 using "SAICAS" manufactured by Daipla Wintes Co., Ltd. to obtain a cross section by stretching each layer, and then the absorption spectrum of the easy-adhesion layer is obtained by microscopic infrared spectroscopy, whereby the blending ratio of the resin and crosslinking agent in the easy-adhesion layer can be obtained.

[0045] The easy-adhesion layer may contain components other than the crosslinked body described above. Examples of other components include uncrosslinked resins, uncrosslinked crosslinking agents, additives, inorganic particles, organic particles, organic-inorganic hybrid particles, and the like. Examples of the additives include antistatic agents, hindered amine weathering agents, and ultraviolet absorbing agents.

[0046] In one embodiment, the easy-adhesion layer is made of only the crosslinked body or substantially made of only the crosslinked body. In the latter case, the easy-adhesion layer may contain unavoidable impurities. In one embodiment, the easy-adhesion layer is 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, 99.5% by mass or more, 99.9% by mass or more, or 100% by mass. Is it a crosslinked body? The crosslinked component and one or more components selected from the other components described above.

[0047] In one embodiment, the glass transition temperature of the easy-adhesion layer is −100° C. or higher and 100° C. or lower, which effectively prevents cracks during thermoforming or long-term use. The glass transition temperature of the easy-adhesion layer can be determined, for example, by measuring a differential scanning calorimetry curve under the following conditions using a differential scanning calorimeter ("DSC-7" manufactured by PerkinElmer Japan Co., Ltd.). Measurement start temperature: -90℃ End of measurement temperature: 220℃ Temperature rise: 10℃ / min

[0048] In one embodiment, the tensile elongation at break of the easy-adhesion layer is 150% or more, 200% or more, or 300% or more, and 900% or less, 850% or less, or 750% or less. When the tensile elongation at break of the adhesive layer is 150% or more, the adhesive layer can easily follow the elongation of the resin layer during thermoforming, so that cracking of the adhesive layer and cracking or peeling of the printed layer can be suppressed. When the tensile elongation at break is 900% or less, the water resistance is good. The tensile elongation at break of the easy-adhesion layer is evaluated, for example, by applying a coating liquid having the same composition as that used when forming the easy-adhesion layer onto a glass substrate using a bar coater, drying at 80°C for 1 minute, and then separating the obtained easy-adhesion layer from the glass substrate to prepare a sample having a thickness of 150 µm, and measuring the elongation at break according to a method in accordance with JIS K7311:1995.

[0049] In one embodiment, the softening temperature of the easy-adhesion layer is 50° C. or more, 90° C. or more, or 100° C. or more, and 180° C. or less, 170° C. or less, or 165° C. or less. When the softening temperature is 50° C. or higher, the adhesive layer has excellent strength at room temperature and can suppress cracking and peeling of the printed layer.When the softening temperature is 180° C. or lower, the adhesive layer is sufficiently softened during molding, so that cracking of the adhesive layer and cracking and peeling of the printed layer can be suppressed. The softening temperature of the easy-adhesion layer is evaluated, for example, by applying a coating liquid having the same composition as that used when forming the easy-adhesion layer onto a glass substrate using a bar coater, drying at 80°C for 1 minute, and then separating the obtained easy-adhesion layer from the glass substrate to prepare a sample having a thickness of 150 µm. The softening temperature of the easy-adhesion layer is measured as the flow start temperature using a high-speed flow tester (Shimadzu Corporation's "Constant Test Force Extrusion Type Capillary Rheometer Flow Tester CFT-500EX").

[0050] The easy-adhesion layer may be a single layer alone or may have a laminated structure of two or more layers. In one embodiment, the thickness of the easy-adhesion layer (the thickness of the laminated structure when there are two or more layers) is 10 nm or more, 20 nm or more, or 30 nm or more, and 3000 nm or less, 2000 nm or less, 1000 nm or less, 800 nm or less, 500 nm or less, 300 nm or less, or 200 nm or less.

[0051] The method for forming the easy-adhesion layer is not particularly limited, and the easy-adhesion layer can be formed by, for example, a coating method. When using the coating method, for example, a coating liquid containing a crosslinking agent Y and a resin is applied onto the resin layer, and the resin is crosslinked by the crosslinking agent Y to form an easy-adhesion layer. The coating liquid may optionally contain a solvent, and the solvent may be dried after coating. For example, a gravure coater, a kiss coater, a bar coater, or the like may be used to apply the coating liquid. For crosslinking and drying, heating may be performed, but may be performed at room temperature (20° C.) When heating is performed, the temperature may be 150° C. or lower, 130° C. or lower, or 100° C. or lower, and may be 30° C. or higher, 35° C. or higher, or 40° C. or higher. The crosslinking time (which may also serve as the drying time) is not particularly limited and may be set appropriately, for example, from 10 seconds to 3 days. Since the crosslinking agent Y is capable of crosslinking at a relatively low temperature, crosslinking can proceed even at the low temperature mentioned above. In this way, since the crosslinking agent Y can be crosslinked at a relatively low temperature, the easy-adhesion layer can be formed on the resin layer at a relatively low temperature. Therefore, the whitening prevention property of the polypropylene X (the property of preventing the whitening of the resin layer due to molding) can be prevented from being impaired when the easy-adhesion layer is formed. As a result, the whitening prevention property of the polypropylene X can be well maintained until the time of molding, and moldability can be further improved.

[0052] [Coating layer] The laminate including the resin layer and the easy-adhesion layer described above can be coated. The coated laminate includes the resin layer, the easy-adhesion layer, and a coating layer formed by coating. According to the present invention, it is possible to prevent the design provided by the coating layer from being damaged during coating or molding. The coating method is not particularly limited, and examples thereof include printing, painting, coating, etc. A printed layer can be formed as a coating layer by printing. A painted layer can be formed as a coating layer by painting. A coating layer can be formed as a coating layer by coating. Each layer will be described in detail below.

[0053] In one embodiment, the laminate includes a printing layer. The printing layer can be provided on the surface of the easy-adhesion layer opposite to the resin layer. The printing layer may be provided on a part of the surface or on the entire surface. The shape of the printing layer is not particularly limited, and may be, for example, a solid shape, a carbon pattern, a wood grain pattern, or various other shapes. As the printing method, general printing methods such as screen printing, inkjet printing, offset printing, gravure printing, roll coating, spray coating, etc. In particular, the inkjet and screen printing methods can make the ink film thicker, so ink cracks are less likely to occur when the material is molded into a complex shape. For example, in the case of screen printing, inks that have excellent elongation during molding are preferred, and examples thereof include "FM3107 High Density White" and "SIM3207 High Density White" manufactured by Jujo Chemical Co., Ltd., but are not limited to these. For example, in the case of inkjet printing, inks with excellent elongation during molding are preferred, and examples of inks include "KVIJET Black KV004," "KVIJET cyan KV215," "KVIJET magenta KV867," "KVIJET yellow KV052," and "KVIJET white KV021" manufactured by Fujifilm Corporation, but are not limited to these.

[0054] In one embodiment, the laminate includes a coating layer. The coating layer can be provided on the surface of the easy-adhesion layer opposite to the resin layer. The coating layer may be provided on a part of the surface or on the entire surface. The design of the coating layer is not particularly limited, and examples thereof include clear, pearl, metallic, and colored. As the coating method, general coating methods such as spray coating, electrodeposition coating, dip coating, electrostatic coating, etc. In particular, spray coating and electrostatic coating are suitable for coating a molded body because of their high coating efficiency and the possibility of automation. For example, in the case of spray painting, a paint that is excellent in preventing scratches on the molded product is preferable, and an example of the paint that can be used is "HMK-003" manufactured by Natoco Co., Ltd., but is not limited to this.

[0055] In one embodiment, the laminate includes a coating layer. The coating layer can be provided on the surface of the easy-adhesion layer opposite to the resin layer. The coating layer may be provided on a part of the surface or on the entire surface. The coating layer is not particularly limited, and examples thereof include, but are not limited to, a hard coat, a self-repair coat, an anti-glare coat, an anti-reflective coat, an antistatic coat, an antifouling coat, an anti-fog coat, and a water-repellent coat.

[0056] 2. Molded body The molded article according to one aspect of the present invention is produced using the laminate according to one aspect of the present invention. In one embodiment, the molded article is produced by molding a laminate by a method such as thermoforming. In one embodiment, the molded body is given a shape that includes a three-dimensional curved surface.

[0057] 3. Manufacturing method of molded body The method for producing a molded article according to one aspect of the present invention includes molding a laminate. Examples of the molding method include in-mold molding, insert molding, and cover molding.

[0058] In-mold molding is a method in which a laminate is placed in a mold and molded into a desired shape by the pressure of a molding resin supplied into the mold to obtain a molded article. In-mold molding is preferably performed by placing the laminate in a mold and supplying molding resin to integrate the laminate.

[0059] In insert molding, the molded object is obtained by preforming the shape of the object to be placed in the mold and filling the molded object with the molding resin. It is possible to form more complex shapes. Insert molding can be performed by shaping the laminate to fit a mold, mounting the shaped laminate in the mold, and supplying molding resin to integrate the laminate. Shaping (pre-shaping) to fit a mold can be performed by vacuum forming, pressure forming, vacuum pressure forming, press forming, plug assist forming, or the like.

[0060] The molding resin may be a moldable thermoplastic resin. Specific examples include, but are not limited to, polypropylene, polyethylene, polycarbonate, acetylene-styrene-butadiene copolymer, acrylic polymer, etc. Inorganic fillers such as fibers and talc may be added to the thermoplastic resin. The supply is preferably carried out by injection, and the pressure is preferably 5 MPa to 120 MPa, and the mold temperature is preferably 20°C to 90°C.

[0061] In covering molding, a core material is placed inside a chamber box, a laminate is placed above the core material, the pressure inside the chamber box is reduced, the laminate is heated and softened, and the laminate is brought into contact with the upper surface of the core material, and the heated and softened laminate is pressed against the core material to cover it. After the heat softening, the laminate may be brought into contact with the upper surface of the core material. Pressing can be performed in a chamber box by applying pressure to the side of the laminate opposite to the core material while keeping the pressure reduced on the side of the laminate that contacts the core material.

[0062] The core material may be convex or concave, and examples thereof include resins, metals, ceramics, etc. having a three-dimensional curved surface. The resin is not particularly limited, and examples thereof include the same thermoplastic resins as those used in the above-mentioned molding.

[0063] For the covering molding, for example, a chamber box consisting of two separable molding chambers, an upper one and a lower one, can be used. First, the core material is placed on the table in the lower molding chamber and set in place. The laminate, which is the object to be molded, is fixed to the upper surface of the lower molding chamber with a clamp. At this time, the pressure inside the upper and lower molding chambers is atmospheric pressure. Next, the upper molding chamber is lowered, the upper and lower molding chambers are joined, and the inside of the chamber box is closed. The inside of both the upper and lower molding chambers is changed from atmospheric pressure to a vacuum suction state by the vacuum tank. After creating a vacuum inside the upper and lower molding chambers, the heater is turned on to heat the laminate. Next, the table in the lower molding chamber is raised while the upper and lower molding chambers are still in a vacuum state. Next, the vacuum in the upper molding chamber is released and atmospheric pressure is introduced, so that the laminate is pressed against the core material and overlaid (molded). It is also possible to apply greater force to the laminate and the core material by supplying compressed air into the upper molding chamber. After the overlay is completed, the heater is turned off, the vacuum in the lower molding chamber is released to return it to atmospheric pressure, the upper molding chamber is raised, and the product covered with the laminate as a skin material is removed.

[0064] The order of coating (forming a coating layer) and shaping of the laminate is not particularly limited. In one embodiment, a coating layer is formed on the easy-adhesion layer in the laminate, and then the laminate including the coating layer is molded. In one embodiment, after the laminate is molded, a coating layer is formed on the easy-adhesion layer of the molded laminate (molded body). Even when forming a coating layer on the easy-adhesion layer of a molded laminate (molded body), the method of forming the coating layer is not particularly limited, and can be performed by painting, printing or coating. In particular, in order to correspond to the curved surface of the molded body, for example, a curved screen printing method or a curved inkjet printing method using an inkjet head attached to a robot arm can be appropriately performed, but is not limited to these examples. EXAMPLES

[0065] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0066] Example 1 (1) Manufacturing of the resin layer Using the device shown in FIG. 1, a resin sheet (resin layer) made of polypropylene was produced. The operation of this device will be described. Molten resin (polypropylene) extruded from a T-die 12 of an extruder is sandwiched between a metallic endless belt 17 and a fourth cooling roll 16 on a first cooling roll 13. In this state, the molten resin is pressed against the first and fourth cooling rolls 13 and 16 and rapidly cooled. The resin sheet is then sandwiched between the metallic endless belt 17 and the fourth cooling roll 16 at a circular arc portion corresponding to the approximately lower half of the fourth cooling roll 16 and pressed against each other. After being pressed against each other and cooled by the fourth cooling roll 16, the resin sheet in close contact with the metallic endless belt 17 is moved onto the second cooling roll 14 as the metallic endless belt 17 rotates. As described above, the resin sheet is pressed against the metallic endless belt 17 at a circular arc portion corresponding to the approximately upper half of the second cooling roll 14 and is cooled again. The resin sheet 11 cooled on the second cooling roll 14 is then peeled off from the metallic endless belt 17. The surfaces of the first and second cooling rolls 13 and 14 are covered with an elastic material 22 made of nitrile-butadiene rubber (NBR). The third cooling roll 15 also functions to support and rotate the metallic endless belt 17 from below.

[0067] The manufacturing conditions for the resin sheet are as follows. Extruder diameter: 150mm Width of T-die 12: 1400mm Polypropylene: Product name: Prime Polypro F-133A, manufactured by Prime Polymer Co., Ltd. (Melt flow index 3g / 10min, homopolypropylene) Thickness: 200μm Take-up speed of resin sheet 11: 25 m / min Surface temperature of the fourth cooling roll 16 and the metallic endless belt 17: 17°C Cooling rate: 10,800℃ / min

[0068] The obtained resin sheets were evaluated as follows.

[0069] (Measurement of crystallization rate) The crystallization rate of the resin layer was measured using a differential scanning calorimeter (DSC) (PerkinElmer's "Diamond DSC"). Specifically, the resin layer was heated from 50°C to 230°C at 10°C / min, held at 230°C for 5 minutes, cooled from 230°C to 130°C at 80°C / min, and then held at 130°C for crystallization. Measurement of the change in heat quantity was started when the temperature reached 130°C, and a DSC curve was obtained. The crystallization rate was calculated from the obtained DSC curve by the following steps (i) to (iv). (i) The baseline was determined by approximating the change in heat quantity from a point 10 times the time from the start of measurement to the peak top to a point 20 times the time by a straight line. (ii) The intersection points between the tangent line having a slope at the inflection point of the peak and the baseline were determined, and the crystallization start and end times were calculated. (iii) The time from the obtained crystallization start time to the peak top was measured as the crystallization time. (iv) The crystallization rate was calculated from the reciprocal of the obtained crystallization time.

[0070] (Measurement of isotactic pentad fraction) Regarding the polypropylene used in the resin layer 13 The isotactic pentad fraction was measured by evaluating the C-NMR spectrum. Specifically, the peak assignments proposed by A. Zambelli et al. in "Macromolecules, 8, 687 (1975)" were followed under the following conditions. As a result of the measurement, the isotactic pentad fraction of polypropylene was 98 mol%. (Measurement method / conditions) Device: 13 C-NMR device (JNM-EX400, manufactured by JEOL Ltd.) Method: Proton complete decoupling method (concentration: 220 mg / ml) Solvent: 90:10 (volume ratio) mixture of 1,2,4-trichlorobenzene and heavy benzene Temperature: 130℃ Pulse width: 45° Pulse repetition time: 4 seconds Accumulation: 10,000 times (calculation formula) Isotactic pentad fraction [mmmm] = m / S × 100 S: signal intensity of the side chain methyl carbon atom of all propylene units m: Mesopentad chain: 21.7-22.5 ppm

[0071] (2) Manufacturing of easy-adhesion layer A coating liquid for forming an easy-adhesion layer was obtained by mixing 100 parts by mass of a urethane resin (product name "Hydran WLS-202", manufactured by DIC Corporation) with 29.3 parts by mass (solid content basis) of a crosslinking agent (product name "Carbodilite V-10", manufactured by Nisshinbo Chemical Inc., a crosslinking agent having a carbodiimide group). After subjecting the resin layer obtained in "(1) Production of resin layer" to a corona treatment, the coating liquid for forming an easy-adhesion layer obtained above was applied by a direct gravure coater so that the film thickness after drying would be 140 nm, and the coating was dried at 80°C for 1 minute to form an easy-adhesion layer. In this manner, a laminate in which the resin layer and the easy-adhesion layer were laminated was obtained.

[0072] (3) Coating (spray painting) The obtained laminate was preliminarily shaped by vacuum pressure molding using a vacuum pressure molding machine ("FM-3M / H" manufactured by Minos Co., Ltd.). This preliminarily shaped body was placed in an injection molding machine ("IS-80EPN" manufactured by Toshiba Machine Co., Ltd.) so that the easy-adhesion layer side of the preliminarily shaped body was in contact with the mold, and polypropylene ("J-106G" manufactured by Prime Polymer Co., Ltd.) was insert molded to produce a molded body. A clear coat (HMK-003, manufactured by Natoco Corporation) was applied to the adhesive layer side of this molded body by air spraying so that the film thickness after drying would be 25 μm, and the coating was dried at 80° C. for 60 minutes to form a coating layer.

[0073] (Evaluation of Coatability) The obtained molded articles were subjected to the following evaluations, and the results are shown in Table 1. (Adhesion) Using a cutter knife, 11 cuts were made at 1 mm intervals in the coating layer of the obtained molded body. In addition, 11 more cuts were made at 1 mm intervals perpendicular to the first cuts to create a 10 x 10 grid. Commercially available cellophane tape ("CT-24" (width 24 mm) manufactured by Nichiban Co., Ltd.) was applied over the cuts and firmly adhered with the pad of a finger, after which the cellophane tape was peeled off. The adhesion was evaluated as a percentage (number of remaining grids / total number of grids (100 grids)).

[0074] (Appearance after coating) The appearance of the obtained molded product was visually observed and evaluated according to the following criteria. A: No bleeding, unevenness, streaks, repelling or whitening occurs. B: One or more of the following has occurred: bleeding, unevenness, streaks, repelling, and whitening. In addition, molded articles rated "B", which are characterized by the occurrence of one or more of the following: bleeding, unevenness, streaks, repelling, and whitening, cannot be said to have a high design quality, and the laminate used is therefore unsuitable for use as, for example, a decorative sheet.

[0075] Example 2 (1) Resin layer and easy-adhesion layer Except for changing the thickness to 300 μm, a resin layer was produced in the same manner as in Example 1. In addition, an easy-adhesion layer was formed in the same manner as in Example 1, and a laminate in which the resin layer and the easy-adhesion layer were laminated was obtained.

[0076] (2) Coating (inkjet printing) An inkjet ink ("KVIJET Black KV004" manufactured by FUJIFILM Corporation) was printed on the adhesive layer side of the obtained laminate using an inkjet printer ("Acuity EY" manufactured by FUJIFILM Corporation) to form a coating layer (printed layer).

[0077] (3) Evaluation of coatability The coatability of the obtained laminate was evaluated according to the same criteria as in (Evaluation of Coatability) of Example 1. The results are shown in Table 1.

[0078] (4) Manufacturing of Molded Products The obtained laminate (having a coating layer) was thermoformed by vacuum pressure molding using a vacuum pressure molding machine ("FM-3M / H" manufactured by Minos Corporation) to produce a molded article.

[0079] (5) Evaluation of the molded product The obtained molded products were subjected to the following evaluations, and the results are shown in Table 1. (Cracks in coating layer) The coating layer of the obtained molded article was visually observed to check the presence or absence and number of cracks in the coating layer, and evaluated according to the following criteria. A: No cracks were observed. B: 1 to 10 cracks occurred. C: 11 to 20 cracks occurred. D: 21 or more cracks occurred.

[0080] (Peeling of coating layer) The coating layer of the obtained molded body was visually observed to determine whether or not there was peeling in the coating layer and the area of ​​the peeled parts was measured. The (area of ​​peeled coating layer / area of ​​the part of the molded body where the laminate was provided) was expressed as a percentage and evaluated according to the following criteria. A: No peeling occurred. B: The peeled area was more than 0% and less than 10%. C: The peeled area was 10% or more and less than 25%. D: The peeled area was 25% or more.

[0081] [Whitening] The obtained molded article was visually observed to check whether or not the resin layer had become white due to the molding process, and was evaluated according to the following criteria. A: No whitening of the resin layer occurred. B: Whitening of the resin layer occurred. In addition, when the resin layer is rated "B" and whitened, the reproducibility of the design is low, and the molded product cannot be said to be of good quality.

[0082] Inkjet printing is performed on the laminate before molding, and then molding is usually performed together with the coating layer, so the coating layer is affected by deformation and other effects associated with the molding process. Therefore, for the examples and comparative examples in which inkjet printing was performed, the results of the above "Evaluation of Molded Product" that reflect this effect are shown. In Comparative Example 4 described below, spray painting was performed, but whitening occurred in the area where the polyolefin resin layer was stretched during molding, resulting in a loss of the design of the molded product after painting, so the evaluation result of "whitening" in the above "Evaluation of Molded Product" is shown.

[0083] Example 3 A laminate was produced and evaluated in the same manner as in Example 1, except that the crosslinking agent was changed to the product name "Epocross WS-500" (a crosslinking agent having an oxazoline group, manufactured by Nippon Shokubai Co., Ltd.) and the amount of crosslinking agent was changed to 15.4 parts by mass (solid content basis) per 100 parts by mass of the urethane resin. The results are shown in Table 1.

[0084] Example 4 Except for changing the blending amount of the crosslinking agent to 14.3 parts by mass (solid content basis) per 100 parts by mass of the urethane resin, the same procedure was followed as in Example 1. A laminate was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0085] Example 5 Except for changing the blending amount of the crosslinking agent to 7.14 parts by mass (solids basis) per 100 parts by mass of the urethane resin, a laminate was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0086] Example 6 (1) Resin layer and easy-adhesion layer A resin layer and an easy-adhesion layer were formed in the same manner as in Example 2, except that the thickness of the resin layer was set to 200 μm, and a laminate in which the resin layer and the easy-adhesion layer were laminated was obtained.

[0087] (2) Coating (wire bar coating) A two-component curing clear paint ("Forseed No. 940C-ZF1" manufactured by Chugoku Paint Co., Ltd.) was applied to the adhesive layer side of the obtained laminate using a wire bar coater so that the film thickness after drying would be 20 μm, and then dried at 80°C for 40 minutes to form a coating layer.

[0088] (3) Evaluation of laminates, production and evaluation of molded products The obtained laminate was evaluated in the same manner as in Example 2. In addition, a molded article was produced from the obtained laminate and evaluated in the same manner as in Example 2. The results are shown in Table 1.

[0089] Example 7 A laminate in which a resin layer and an easy-adhesion layer were laminated was obtained in the same manner as in “(1) Resin layer and easy-adhesion layer” of Example 6. A UV-curable hard coat agent (Lioduras MOL-9000 manufactured by Toyochem Co., Ltd.) was applied to the easy-adhesion layer side of the obtained laminate using a wire bar coater so that the film thickness after drying would be 5 μm, and after drying at 80° C. for 1 minute, the coating layer was cured with UV light using a high-pressure mercury lamp to form a coating layer. The obtained laminate was evaluated in the same manner as in Example 6. A molded article was also produced and evaluated in the same manner as in Example 6. The results are shown in Table 1.

[0090] Comparative Example 1 Except for omitting the incorporation of the crosslinking agent and forming an easy-adhesion layer consisting only of a urethane resin, a laminate was produced and evaluated in the same manner as in Example 1. The results are shown in Table 1. Whitening occurred in the obtained laminate.

[0091] Comparative Example 2 Except for omitting the incorporation of the crosslinking agent and forming an easy-adhesion layer consisting only of a urethane resin, a laminate and a molded product were produced and evaluated in the same manner as in Example 2. The results are shown in Table 1. Bleeding and unevenness occurred on the laminate after coating.

[0092] Comparative Example 3 Except for omitting the easy-adhesion layer, a laminate and a molded product were produced and evaluated in the same manner as in Example 2. The results are shown in Table 1. It was confirmed that the coating layer after coating had no adhesion.

[0093] Comparative Example 4 A laminate was produced and evaluated in the same manner as in Example 1, except that a nucleating agent (product name "Rikemaster FC-2" manufactured by Riken Vitamin Co., Ltd., a sorbitol-based nucleating agent) was added in an amount of 1.5% by mass based on the total amount of the resin layer. The results are shown in Table 1. Using the obtained laminate, a molded article was produced in the same manner as in Example 2, and the presence or absence of whitening was evaluated. Whitening occurred in the area where the polyolefin resin layer was stretched during molding, resulting in a loss of the design of the molded article after painting.

[0094] Comparative Example 5 Except for omitting the easy-adhesion layer, a laminate and a molded product were produced and evaluated in the same manner as in Example 6. The results are shown in Table 1. It was confirmed that the coating layer after coating had no adhesion.

[0095] Comparative Example 6 Except for omitting the easy-adhesion layer, a laminate and a molded product were produced and evaluated in the same manner as in Example 7. The results are shown in Table 1. It was confirmed that the coating layer after coating had no adhesion.

[0096] [Table 1] [Industrial Applicability]

[0097] The molded article obtained from the laminate of the present invention can be used in a wide variety of applications, for example, as a decorative sheet replacing paint on housings in a wide variety of fields such as transportation equipment (automobiles, motorcycles, etc.), housing equipment, building materials, and home appliances.

[0098] Although some embodiments and / or examples of the present invention have been described in detail above, those skilled in the art can easily make many modifications to these exemplary embodiments and / or examples without substantially departing from the novel teachings and advantages of the present invention, and therefore many such modifications are within the scope of the present invention. The contents of all documents cited in this specification and of the application from which this application claims priority under the Paris Convention are incorporated by reference in their entirety.

Claims

1. Crystallization speed at 130°C is 2.5 min -1 A laminate comprising a resin layer containing the following polypropylene and an easy-adhesion layer, the easy-adhesion layer includes a crosslinked body obtained by crosslinking a resin with a crosslinking agent having one or more groups selected from the group consisting of a carbodiimide group, an oxazoline group, and an aziridine group, The resin in the easy-adhesion layer contains one or more resins selected from the group consisting of urethane resins, polyolefin resins, and polyester resins, No other resin layer is included between the resin layer and the easy-adhesion layer. Laminate.

2. The laminate according to claim 1 , wherein the crosslinking agent is a crosslinking agent having a carbodiimide group.

3. The laminate described in claim 1, wherein the crosslinking agent is a crosslinking agent having one or more groups selected from the group consisting of an oxazoline group and an aziridine group.

4. The laminate according to any one of claims 1 to 3, wherein the resin in the easy-adhesion layer comprises a urethane resin.

5. 5. The laminate according to claim 1, wherein the amount of the crosslinking agent is 2 to 50 parts by mass with respect to 100 parts by mass of the resin.

6. 6. The laminate according to claim 1, wherein the polypropylene has an isotactic pentad fraction of 80 mol % or more and 99 mol % or less.

7. The laminate according to any one of claims 1 to 6, wherein the resin layer does not contain a nucleating agent.

8. The laminate according to any one of claims 1 to 7, further comprising a coating layer on a part or the entire surface of the easy-adhesion layer opposite the resin layer.

9. The laminate according to any one of claims 1 to 8, further comprising a printed layer on a part or the entire surface of the easy-adhesion layer opposite the resin layer.

10. The laminate according to any one of claims 1 to 8, further comprising a coating layer on a part or the entire surface of the easy-adhesion layer opposite to the resin layer.

11. A molded article produced using the laminate according to any one of claims 1 to 10.

12. A method for producing a molded article, comprising molding the laminate according to any one of claims 1 to 10.

13. The method for producing a molded article according to claim 12, further comprising the steps of: mounting the laminate in a mold; supplying a molding resin to be integrated with the laminate; and carrying out the molding.

14. The method for producing a molded body according to claim 12, further comprising shaping the laminate to fit a mold, mounting the shaped laminate in the mold, and supplying a molding resin to integrate with the shaped laminate to perform the molding.

15. A method for producing a molded body as described in claim 12, comprising disposing a core material in a chamber box, placing the laminate above the core material, heating and softening the laminate, and reducing the pressure inside the chamber box to press the heat-softened laminate against the core material to cover it.

16. A method for producing a molded body, comprising painting a part or the entire surface of the easy-adhesion layer of the molded body produced by the method for producing a molded body according to any one of claims 12 to 15, opposite to the resin layer.

17. A method for producing a molded body, comprising printing on a part or the entire surface of the easy-adhesion layer of the molded body produced by the method for producing a molded body according to any one of claims 12 to 15, opposite to the resin layer.

Citation Information

Patent Citations

  • Easily bondable thermoplastic resin film

    JP2011152783A

  • Printable coating

    JP2016006181A

  • Printing sheet

    JP2016168685A

  • Laminate, molding, and method for producing molding

    JP2017149144A

  • Acrylic resin composition, acrylic film, decorative film and decorative molding body

    JP2018065947A